Estimates of genetic parameters and genetic trends for live weight and fleece traits in Menz sheep - Solomon G.; Sisay L.; Hans K.; Arendonk, Johan A.M. van (Elsevier, 2007)
Menz sheep are indigenous to the highlands of Ethiopia, and highly valued for their meat and wool production. The area is characterized as a low input mixed barley-sheep production system. In 1998, a selection experiment was setup to evaluate the response of Menz. sheep to selection for yearling live weight (WTI2) and greasy fleece weight (GFW) combined in an economic index. In this paper, we report the results of this breeding program obtained between 1998 and 2003. Average annual genetic selection responses for WT12 and GFW were 1.506 and 0.043 kg in the selected flock and 0.392 and -0.008 kg in the control flock. Annual genetic trends in the selected flock, estimated by regressing BLUP estimated breeding values on year of birth, were 0.495 ± 0.053 kg for WT12, 0.012 ± 0.002 kg for GFW, and Birr 5.53 ± 0.55 for the aggregate breeding value (1 Ethiopian Birr = 0.115 USD). Corresponding values for the control flock were 0.276±0.065 kg, 0.003±0.002 kg and Birr 2.93±0.69. Correlated responses in birth weight (WTO), weaning weight (WT3), 6-month weight (WT6) and staple length (STPL) in the selected flock were 0.038±0.005 kg, 0.271 ± 0.03 kg, 0.388 ± 0.039 kg and 0.011 ± 0.017 cm. respectively. Heritabilities, estimated by fitting a multitrait individual animal model were 0.464 ± 0.014, 0.477 ± 0.016, 0.514 ± 0.017, 0.559 ± 0.019, 0.393 ± 0.016 and 0.339 ± 0.014 for WTO, WT3, WT6, WT12, GFW and staple length (STPL), respectively. Phenotypic and genetic correlations between all traits were positive, except for STPL and WT12. Estimates of genetic parameters and observed genetic trends confirm that selective breeding can lead to significant genetic improvement in Menz sheep.